Pengaruh Reaksi Difusi-Adveksi pada Sistem Pemangsa-Mangsa - Maulana Asrafi; Sutrima (Limits: Journal of Mathematics and Its Applications, 2026)
The predator-prey system is a model of interspecies interaction dynamics that is naturally influenced by environmental factors such as diffusion and advection. In the context of ecology, diffusion represents the spread of populations due to random movement from high to low concentrations, while advection models the influence of directed external flows such as river currents or wind. This study aims to examine the effect of the combination of these two reactions on the stability of the equilibrium point of the system through theoretical analysis and literature review. The results show that the presence of diffusion-advection significantly changes the stability conditions, particularly at equilibrium points  and .  Bifurcation analysis reveals the occurrence of Turing instability and Hopf bifurcation at certain parameter values. Biologically, this phenomenon indicates that disturbances in environmental flows can trigger the formation of uneven population distribution patterns (spatial heterogeneity) and population fluctuations that oscillate over time. This finding confirms that predatory interactions are highly sensitive to physical environmental parameters that go beyond purely biological interactions.